Caracterização da caprinovinocultura em Minas Gerais. - Alessandro de Sa Guimaraes (2006)
The caprine and ovine farming was characterized in Minas Gerais, in order to determine the general aspects of the products, health and socioeconomic aspects, using the analysis of questionnaires and direct observation of the properties. Four hundred and ninety-seven properties were studied, being two hundred and eighty located in four esorregions, Noroeste de Minas, Norte de Minas, Jequitinhonha e Vale do Mucuri (Norte) and two hundred and seventeen located in eight mesorregions, Campo das Vertentes, Central Mineira, Metropolitana de Belo Horizonte, Oeste de Minas, Sul/Sudoeste de Minas, Triângulo/Alto Paranaíba, Vale do Rio Doce e Zona da Mata (Centro Oeste Sul). One hundred and ninety-two Norte mesorregions properties and eighty COS kept only goats. Thirteen variables were selected for the determination of the technological level with scares 1,2 or 3, as a function of complexity andtechnical knowledge for its implantation. The technological level was calculated dividing the scores obtained by the property (multiplied by 100) by the total maximum possible score (22 for goats and 26 for sheep). Properties which obtained scores between 0 and 33% were classifiedas poorly technified, between 34 and 63% were classified as average and those with scores between 65 and 100% as high. Among the 219 properties with goats and 117 with sheep, only 15 (6,8%) and two (1,7%), respectively, were considered employing high technology. The results indicated that caprine and ovine farming in Minas Gerais have low level technology aspects.